House prices and rents in the 21st century - Lara Loewenstein; Paul Willen (Federal Reserve Bank of Boston, 2023)
We study the joint evolution of prices and rents of residential property. After constructing rent and price indices for renter- and owner-occupied properties, we decompose the change in the price of occupant-owned property into (1) changes in rent, (2) changes in the relative prices of investor- and occupant-owned properties, and (3) changes in the price-rent ratio. Via a simple model, we link our decomposition to different sources of variation in house prices. We argue that while the 2000s boom was plausibly driven by exuberant expectations, the boom of the 2020s more likely resulted from a preference shock.
Keywords: R30; R31; E30; E32; H31; 330; house price overvaluation; rent-price ratio; credit shocks; housing bubbles; Wohnimmobilien; Immobilienmarkt; Miete; Immobilienpreis; Spekulationsblase; USA